A comparative 30‐day outcome analysis of inpatient evaluation vs outpatient testing in patients presenting with chest pain in the high‐sensitivity troponin era. A propensity score matched case‐control retrospective study. Issue 11 (4th August 2020) - Mahmoud, Osama; Mahmaljy, Hadi; Elias, Hadi; Campoverde, Edwin Hernandez; Youniss, Mohamed; Stanton, Matthew; Young, Katelyn; Patel, Maulin; Kuppuraju, Rajesh; Jacobs, Steven; Hashmi, Insia; Alsaid, Amro
Abstract: Background: The best disposition of chest pain patients who rule out for myocardial infarction (MI) but have non‐low clinical risk scores in the high‐sensitivity troponin era is not well studied. Hypothesis: In carefully selected patients who rule out for MI, and have a high‐sensitivity troponin T ≤ 50 ng/L with an absolute increase less than 5 ng/L on repeat measurements, early emergency room (ER) discharge might be equivalent to inpatient evaluation in regards to 30‐day incidence of adverse cardiac events (ACEs) regardless of the clinical risk score. Methods: A total of 12 847 chest pain patients presenting to our health system ERs from January 2017 to September 2019 were retrospectively investigated. A propensity score matching algorithm was used to account for baseline differences between admitted and discharged cohorts. We then estimated and compared the incidence of 30‐day and 1‐year composite ACEs (MI, urgent revascularization, or cardiovascular death) between both groups. A multivariate Cox regression model was used to evaluate the effect of admission on outcomes. Results: A total of 2060 patients were matched in 1:1 fashion. The primary endpoint of 30‐day composite ACEs occurred in 0.6% and 0.4% of the admission and the discharged cohorts, respectively ( P = .76). One‐year composite ACEs was also similar between both groups (4% vs 3.7%, P = .75). In a multivariate Cox regression model, the effect of inpatient evaluation was neutral (hazard ratio 1.1, confidence interval 0.62‐1.9, P = .75). Conclusions: Inpatient evaluation was not associated with better outcomes in our selected group of patients. Larger‐scale randomized trials are needed to confirm our findings.